Innovation, conformity and other ambivalences in fashion design (ModaPalavra e-periódico, 2021)
This article problematizes the creation in fashion design. A noticeable majority of companies in the fashion market accompanies trends, which are edited by bureaux de style, disseminated by fashion designers at week runway shows and advertised as successful bets by the fashion media. This investigation results from the development of a research about the agency of fashion designers. The given scope emphasizes the dialectics of creation x adequacy and innovation x security. More specifically, the paper addresses the considerations of three interviewees conducted for the validation of the research’s results. During the dialogues - which consisted of informal telephone conversations aided by a semi-structured script – the professionals reported their reflections on deliberate acts of creation and the business logic of fashion design corporations.
Keywords: fashion design; creation; innovation